1975
DOI: 10.1056/nejm197503272921301
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Angiotensin II Antagonist (Saralasin) in the Recognition of “Angiotensinogenic” Hypertension

Abstract: The possibility has been explored of using a specific angiotensin ii antagonist, saralasin (P-113, 1-sar-8-ala-angiotensin ii) to recognize patients whose hypertension depends upon excessive angiotensin ii activity. Among 60 hypertensive patients, saralasin infusion reduced blood pressure in 16 "responders," but not in 44 "nonresponders." The "responders" had the following findings: elevated plasma renin activity in renal vein (or veins) or peripheral veins or both (16 of 16); reduced renal blood flow, shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
3

Year Published

1975
1975
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(64 citation statements)
references
References 6 publications
5
56
0
3
Order By: Relevance
“…When the same normals were salt loaded, P113 infusion (5-10 jig kg' min-f) caused a slight rise in lying and standing blood pressure. This effect has been reported in some hypertensives whose blood pressure did not fall during P113 infusion (Streeten et al, 1975). This rise in blood pressure cannot be due to release of renin as PRA decreased during infusion when normals were sodium loaded.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…When the same normals were salt loaded, P113 infusion (5-10 jig kg' min-f) caused a slight rise in lying and standing blood pressure. This effect has been reported in some hypertensives whose blood pressure did not fall during P113 infusion (Streeten et al, 1975). This rise in blood pressure cannot be due to release of renin as PRA decreased during infusion when normals were sodium loaded.…”
Section: Resultssupporting
confidence: 70%
“…However, P113 has been noted to cause a rise in blood pressure in some patients (Streeten et al, 1975), and these presumed agonist (Angiotensin II) effects of P113 have been observed in animal isolated tissues and in sodium loaded rabbits (Mimran, Hinrichs & Hollenberg, 1974). The agonist activity seeming to depend on the tissue studied, the endogenous level of angiotensin II and the sodium intake.…”
Section: Introductionmentioning
confidence: 99%
“…Classification of patients into low, normal, and high PRA subgroups was based On the concomitant 24-hour urine Na excretion as described by Laragh and colleagues. * 9 Upright PRA and PAC determinations on placebo and at 1 hour after the initial and effective doses of captopril were compared.…”
Section: Experimental Designmentioning
confidence: 99%
“…, ala']-angiotcnsin II (saralasin), has been effective in reducing BP in hypertensive patients but its clinical use has been limited by its partial agonistic properties and by the need for parenteral administration. 9 - 10 Recent evidence has suggested that substances that inhibit angiotensin II formation by blockade of angiotensin I converting enzyme may be clinically useful antihypertensive agents. 11 A nonapeptide, teprotide (SQ 20,881, BPF e .…”
mentioning
confidence: 99%
“…The first developed Ang I1 receptor antagonists were peptide analogs of Ang 11, e.g., saralasin (Sarl, Ala8-Ang 11) (40). These peptide antagonists were partial agonists and lacked oral bioavailability, however, and were not suitable for clinical use.…”
Section: Introductionmentioning
confidence: 99%